Repair Cafés as Circular Economy Enablers: Exploring Participants Practices through Social Practice Theory - Markussen, Tanja; Jørgensen, Michael S.; Dorland, Jens; Laursen, Linda Nhu; Hansen, Andreas Kornmaaler (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
In this paper, we study the repair practices in Danish repair cafés, to understand how repair activities initiated by civil society are organized and sustained within broader social and material contexts. By applying Social Practice Theory, the analysis dissects the interconnected elements of materials, competencies, and meanings that constitute and shape the ongoing practice of repair in Danish Repair cafés. The repair practices form part of "bundles" of interconnected practices within the repair cafes. The study demonstrates that repair cafés are more than spaces for fixing broken items; they hold broader societal and cultural aspects. Through the interconnectedness of repair, learning, and community-building practices, these cafés challenge the "throwaway culture" and foster a collective commitment to sustainability that potentially could have implications far beyond their immediate settings.